2019
DOI: 10.1002/jor.24405
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Measurement of Thumb Joint Reaction Forces During Smartphone Manipulation: A Biomechanical Analysis

Abstract: The relationship between arthritis or repetitive stress injuries (RSIs) in thumbs and rapidly increasing hours of smartphone usage is not fully elucidated. We evaluated axial joint reaction forces (AJRFs) and thumb torques in 19 healthy subjects performing typical smartphone tasks, which included tapping, tap game, and swiping. We measured force and torque when a subject tapped or swiped the panel of the smartphone and analyzed the motions of each joint using surface markers and motion capture systems. We calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…In future research, the mechanical mock-up can be replaced by a mapping from kinematics to kinetics. This is usually accomplished by introducing human motion data to a musculo-skeletal model, and, by means of inverse kinematics and inverse dynamics, compute the internal load state of a human [10], [11]. Since this approach is computationally expensive and infeasible for real-time control, surrogate models might as well be a suitable measure for addressing this problem.…”
Section: Discussionmentioning
confidence: 99%
“…In future research, the mechanical mock-up can be replaced by a mapping from kinematics to kinetics. This is usually accomplished by introducing human motion data to a musculo-skeletal model, and, by means of inverse kinematics and inverse dynamics, compute the internal load state of a human [10], [11]. Since this approach is computationally expensive and infeasible for real-time control, surrogate models might as well be a suitable measure for addressing this problem.…”
Section: Discussionmentioning
confidence: 99%
“…4 Considering the rapid increase in the use of mobile smartphone devices, the incidence of TMC arthritis is also expected to increase. 5 Trapeziectomy is the most popular surgical technique performed for TMC arthritis. The procedure is, however, criticized for weakening lateral pinch strength.…”
Section: Introductionmentioning
confidence: 99%
“…The motion results in compressive rotational shear force at the trapezium 4 . Considering the rapid increase in the use of mobile smartphone devices, the incidence of TMC arthritis is also expected to increase 5 …”
Section: Introductionmentioning
confidence: 99%
“…of the thumb during a lateral pinch. 13,14 Cooney et al 13 reported compression forces of 12 kg during a simple pinch with 1 kg of applied force and 120 kg at the CMC joint during a strong grasp.…”
mentioning
confidence: 99%
“…In biomechanical studies, the joint reaction forces in the CMC joint are twelve times greater than the contact forces at the tip of the thumb during a lateral pinch. 13 , 14 Cooney et al 13 reported compression forces of 12 kg during a simple pinch with 1 kg of applied force and 120 kg at the CMC joint during a strong grasp.…”
mentioning
confidence: 99%